РЕГІОНАЛЬНІ ОСОБЛИВОСТІ ПОЛІТИКИ КОРЕНІЗАЦІЇ (УКРАЇНІЗАЦІЇ) В УСРР: СУЧАСНИЙ СТАН ТА ПЕРСПЕКТИВИ ВИВЧЕННЯ (Zaporizhzhia Historical Review, 2021)
This article is devoted to the analysis of the present historiography concerning the peculiarities of ukrainization policy in UkSSR. The article reveals the main tendencies in studying the problems of Bolshevist National policy realization in Ukraine in 1920s and 1930s. Besides, in this article the perspectives of this topic studying are many-sided theme and outlined out.